2014
DOI: 10.1042/bj20140604
|View full text |Cite
|
Sign up to set email alerts
|

Dynamitin affects cell-surface expression of voltage-gated sodium channel Nav1.5

Abstract: The major cardiac voltage-gated sodium channel Nav1.5 associates with proteins that regulate its biosynthesis, localization, activity and degradation. Identification of partner proteins is crucial for a better understanding of the channel regulation. Using a yeast two-hybrid screen, we identified dynamitin as a Nav1.5-interacting protein. Dynamitin is part of the microtubule-binding multiprotein complex dynactin. When overexpressed it is a potent inhibitor of dynein/kinesin-mediated transport along the microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Cotransfection of p50 increased the I Kir2.1 at potentials between −120 and −90 mV and between −70 and −50 mV (Figures 5B,D ; P < 0.05), suggesting that the dynein/dynactin complex is involved in the retrograde trafficking of Kir2.1 channels. Conversely, p50 reduced the I Nav1.5 at potentials ranging −40 and +30 mV in cells expressing Nav1.5 channels alone (Figures 5C,E ; P < 0.05), thus confirming previous results that demonstrate the role of the dynein/dynactin complex in the anterograde trafficking of Nav1.5 channels (Chatin et al, 2014 ). When Kir2.1 and Nav1.5 channels were expressed together, both I Kir2.1 and I Nav1.5 were significantly increased as expected (Figures 5B–E ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Cotransfection of p50 increased the I Kir2.1 at potentials between −120 and −90 mV and between −70 and −50 mV (Figures 5B,D ; P < 0.05), suggesting that the dynein/dynactin complex is involved in the retrograde trafficking of Kir2.1 channels. Conversely, p50 reduced the I Nav1.5 at potentials ranging −40 and +30 mV in cells expressing Nav1.5 channels alone (Figures 5C,E ; P < 0.05), thus confirming previous results that demonstrate the role of the dynein/dynactin complex in the anterograde trafficking of Nav1.5 channels (Chatin et al, 2014 ). When Kir2.1 and Nav1.5 channels were expressed together, both I Kir2.1 and I Nav1.5 were significantly increased as expected (Figures 5B–E ).…”
Section: Resultssupporting
confidence: 90%
“…The experiments conducted in cells overexpressing the p50 subunit to inhibit the dynein/dynamitin motor complex showed that it is involved in the retrograde and anterograde trafficking of Kir2.1 and Nav1.5 channels, respectively. Our results confirm previous data showing that p50 interacts with Nav1.5 channels reducing their expression at the cell surface and the I Nav1.5 density (Chatin et al, 2014 ). Importantly, our results also suggested that the dynein/dynamitin motor complex is critical for the anterograde trafficking of the pool of Kir2.1 and Nav1.5 channels that form the complexes, supporting the hypothesis that their biology may be similar to that of Nav1.5 channels (Figure 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it has been demonstrated that activation of SAR1 leads to the recruitment and internalization of Na v 1.5 cargo into the coated transition vesicle COPII-coated vesicles that will ensure its ER-to-Golgi trafficking [202]. The Na v 1.5 ER export is also controlled by Dynamitin as demonstrated by Chatin et al, who have proved, using a yeast two-hybrid system, that Dynamitin (C-terminal domain), interacted with the Na v 1.5 DI-DII linker between amino acids 417 and 444 and that this interaction is crucial for the Na v 1.5 cell-surface density probably through controlling the ER-to-Golgi trafficking [203].…”
Section: Regulation Of the Er-to-golgi Traffickingmentioning
confidence: 85%
“…To this end, the yeasts transformed with bait and prey vectors were plated onto a single selective medium lacking Leu-Trp (SC-Leu-Trp) plate at 30°C for 18 h. Afterwards, replicas were sequentially plated (a first incubation at 30°C for 24 h followed by a second incubation at 30°C for 1 d) onto selection plates in the presence of SC-Leu-Trp-His-3AT or SC-Leu-Trp-5FOA. Densitometric analysis of the images was performed using ImageJ to analyze putative changes in the SUR2A–AnkB interaction induced by the p.S1054Y mutation ( Chatin et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%